Cultural Entrepreneurship in Corporate Governance Practice Diffusion: Framing of “Independent Directors” by U.S.-Listed Chinese Companies - Park, Sun Hyun; Zhang, Yanlong (Organization Science, 2020)
Although the diversity of cultural expectations for different corporate governance practices has been acknowledged, our understanding of how companies use cultural differences to legitimize their governance practice choice and facilitate their resource acquisition remains limited. Building on the literature on cultural entrepreneurship, we theorize how foreign-listed firms engage in global framing in tailoring the description of their new governance practice to the host country investors. Our empirical study examines the relative emphasis of monitoring over resource-providing roles by the U.S.-listed Chinese companies’ independent directors when their roles are understood differently in the home and host countries. Our study finds that exposure to the alternative cultural repertoire of a host country via overseas education of board members and foreign institutional ownership enhance a firm’s organizational resources available to engage in global framing. The likelihood of global framing, however, is constrained by the home country’s institutional environment, which is characterized by local business history and connections to strong local resource providers such as the state. We also find that the effectiveness of global framing to obtain investor recognition in the host country is restricted when the company lacks the capacity to implement the declared role of independent director-as-monitor in its home country.